410 Estimating the burden of occupational Chronic Obstructive Pulmonary Disease (COPD) in the UK. (11th October 2013) - Hutchings, S J; Sadhra; Kurmi; De Matteis; Jarvis; Fishwick; Chambers; Mitchell; Gallacher; Wheatley; Cullinan; Rushton
Abstract : Objective: As part of a UK Biobank project to investigate the causes of COPD in the UK, initial estimates have been made of the burden of COPD attributed to occupational exposures, based on methods developed to estimate cancer burden, adapted to a prevalence rather than incidence outcome measure. Methods: Particular features of the methods were inflation of the estimates of numbers employed in occupations linked to COPD to account for retired or ex-workers whose exposure has ceased, and estimating attributable fraction (AF) by age, as COPD incidence increases with age. The link between age and duration of exposure, and time from cessation of exposure are accounted for by using unit relative risk (URR) estimates (annual change in COPD risk) or annual lung function decline. Where URRs are not available, risks are estimated by age based on assumptions about the age structure of a particular worker cohort. Results: Using national data of numbers employed in occupations associated with raised COPD risk, matched to appropriate risk estimates and based on Levin's estimator, when mainly industry-based cross-sectional study risks were used, AFs for GB were estimated to be 11% for men and 3% for women. Alternatively using single population-based studies estimating risks by occupation or industry, AFs range from 6%-27% for men and 0%-5% for women. The probable reasons for the variability of the results are discussed, and an example is given of the additional impact of taking age into account in the estimation. Conclusions: There is consistency between these initial estimates of occupational COPD attribution and previous estimates such as those from the American Thoracic Society. When data from the UK Biobank study becomes available, it is planned to further develop the AF by age methods to use with Miettinen's study based estimator.